2012
DOI: 10.3233/wor-2012-0549-2963
|View full text |Cite
|
Sign up to set email alerts
|

Is occupational stress associated with work engagement ?

Abstract: The occupational stress is associated with dissatisfaction, excessive demand at work and personal factors. Those factors can reduce work performance and can predispose workers to various diseases. Workers' health may be protected if there is encouragement to face challenges, which may lessen the impact on psychological and somatic stress and thus have greater personal and professional satisfaction. The aim of this study was to evaluate the association between occupational stress and work engagement. Participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…As job demands, extrinsic effort was negatively associated with vigor, dedication, and absorption. This finding was consistent with previous studies from different countries [ 26 28 ]. There are two possible explanations for the negative relations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As job demands, extrinsic effort was negatively associated with vigor, dedication, and absorption. This finding was consistent with previous studies from different countries [ 26 28 ]. There are two possible explanations for the negative relations.…”
Section: Discussionsupporting
confidence: 94%
“…There are many researches that have found positive relationships between occupational stress and job burnout in nurses across countries [ 23 25 ]. Occupational stress has been identified as a predictor of work engagement in the workers of a metallurgical industry [ 26 ]. Also, as occupational stressors, workload and time pressure showed a positive association with work engagement among Japanese employees [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This also happened to Bukittinggi City government employees, because of the feeling of being bored or bored at a monotonous and routine job that triggers the emergence of stress in work, as a result there will be a conflict of interest that occurs among fellow employees, namely employees who do not cooperate with employees who work seriously.This study is in line with research conducted by Rothmann, (2008) who revealed no significant relationship between work stress (due to work demand) and work involvement (enthusiasm and dedication). Among the studies of Padula et al (2012) revealed that there is a negative relationship between work stress and work involvement. Furthermore, research conducted by Beattie & Griffin (2014) revealed that impoliteness in the workplace, or rude and disrespectful behavior will cause stress for employees.…”
Section: Resultsmentioning
confidence: 99%
“…This understanding from Marciano (2010) can be interpreted to the extent that a person is committed, dedicates himself and is loyal to the organization, supervisor, work and his colleagues. Padula et al, (2012) revealed that work stress is related to dissatisfaction, excessive demand at work and personal factors. According to Rabiu, Muhammed, Umaru, & Ahmed (2016);Murillo-Zamorano et al, (2019) which states that inverted classes have a positive effect on students' knowledge, skills, and involvement.…”
Section: Work Engagementmentioning
confidence: 99%
See 1 more Smart Citation